Royal throne : the future of the monarchy - Longford, Elizabeth, 1906-2002 (London : Hodder & Stoughton, 1993)
1992 was the most momentous year for the British Royal Family since the abdication of Edward VIII 57 years earlier, fuelling massive media speculation about the very future of the Monarchy--a subject affecting the foundations of the British Constitution. Elizabeth Longford, leading biographer of the Royal House of Windsor, interviewed both named and unnamed sources close to the Royal Family to gather the evidence for this book. It is a pithy and perceptive appraisal of how the image of the Monarchy was affected by recent royal behaviour in public and in private. Lady Longford uses her historical knowledge of previous royal crises to assess the gravity of the situation. She analyses the deeper issues affecting the future of the Royal Family such as the Queen's decision to pay income tax, the curtailment of the Civil List and the separation of the Prince and Princess of Wales.--From publisher description.
Includes index.
Keywords: Elizabeth -- II, -- Queen of Great Britain, -- 1926- -- Family; Windsor, House of; Monarchy -- United Kingdom -- History -- 20th century; United Kingdom -- Kings and rulers -- Succession